Sensorineural deafness and male infertility: a contiguous gene deletion syndrome. Issue 4 (10th November 2006) - Zhang, Yuzhou; Malekpour, Mahdi; Al-Madani, Navid; Kahrizi, Kimia; Zanganeh, Marvam; Mohseni, Marzieh; Mojahedi, Faezeh; Daneshi, Ahmad; Najmabadi, Hossein; Smith, Richard J H
Abstract : Background: Syndromic hearing loss that results from contiguous gene deletions is uncommon. Deafness-infertility syndrome (DIS) is caused by large contiguous gene deletions at 15q15.3. Methods: Three families with a novel syndrome characterised by deafness and infertility are described. These three families do not share a common ancestor and do not share identical deletions. Linkage was established by completing a genome-wide scan and candidate genes in the linked region were screened by direct sequencing. Results: The deleted region is about 100 kb long and involves four genes ( KIAA0377, CKMT1B, STRC and CATSPER2 ), each of which has a telomeric duplicate. This genomic architecture underlies the mechanism by which these deletions occur. CATSPER2 and STRC are expressed in the sperm and inner ear, respectively, consistent with the phenotype in persons homozygous for this deletion. A deletion of this region has been reported in one other family segregating male infertility and sensorineural deafness, although congenital dyserythropoietic anaemia type I (CDAI) was also present, presumably due to a second deletion in another genomic region. Conclusion: We have identified three families segregating an autosomal recessive contiguous gene deletion syndrome characterised by deafness and sperm dysmotility. This new syndrome is caused by the deletion of contiguous genes at 15q15.3.